Muscular adaptations and insulin‐like growth factor‐1 responses to resistance training are stretch‐mediated. Issue 1 (30th October 2013) - McMahon, Gerard; Morse, Christopher I.; Burden, Adrian; Winwood, Keith; Onambélé, Gladys Leopoldine
ABSTRACT Introduction: Modulation of muscle characteristics was attempted through altering muscle stretch during resistance training. We hypothesized that stretch would enhance muscle responses. Methods: Participants trained for 8 weeks, loading the quadriceps in a shortened (SL, 0–50° knee flexion; n = 10) or lengthened (LL, 40–90°; n = 11) position, followed by 4 weeks of detraining. Controls (CON; n = 10) were untrained. Quadriceps strength, vastus lateralis architecture, anatomical cross‐sectional area (aCSA), and serum insulin‐like growth factor‐1 (IGF‐1) were measured at weeks 0, 8, 10, and 12. Results: Increases in fascicle length (29 ± 4% vs. 14 ± 4%), distal aCSA (53 ± 12% vs. 18 ± 8%), strength (26 ± 6% vs. 7 ± 3%), and IGF‐1 (31 ± 6% vs. 7 ± 6%) were greater in LL compared with SL muscles (P < 0.05). No changes occurred in CON. Detraining decrements in strength and aCSA were greater in SL than LL muscles (P < 0.05). Conclusions: Enhanced muscle in vivo (and somewhat IGF‐1) adaptations to resistance training are concurrent with muscle stretch, which warrants its inclusion within training. Muscle Nerve49: 108–119, 2014